Pengembangan Media Pembelajaran Display Berbasis 3D PageFlip dengan Model POE2WE pada Materi Dinamika Rotasi - Nurfa, Nisa Nisriana; Nana, Nana (Jurnal Penelitian Pendidikan Fisika, 2021)
3D PageFlip development is widely used in education and produces a medium that can increase student interest and motivation. Even so, the use of 3D PageFlip is still relatively rare in learning. Lack of socialization on the use of software is said to be the main reason for the lack of use of 3D PageFlip software. Based on this, it is necessary to write about using 3D PageFlip to produce 3D FlipBook as a learning medium. This paper will explain how to make learning media based on 3D Physics PageFlip for Rotation Dynamics material by using model POE2WE.